ULAMA IN INDONESIAN URBAN SOCIETY: A View of Their Role and Position in the Change of Age - Abidin, Muhammad Zainal (Fakulta Ushuluddin dan Humaniora Universitas Islam Negeri Walisongo Semarang, Indonesia, 2017)
Abstract: The purpose of this study is to know how the changes of the social impact the role and the position of the ulama. Urban society is the real phenomena that happen for the coming of the industrialization era, or in another word that the urban society is the manifest of the industrial society. The writer sees the urban society phenomena as similar as the industrial society. This is a library research, which takes the source of study from the books and other literature related to the topic. The source of data is classified into two parts, the primary source, and the secondary one. As analysis technique, the writer uses the content analysis with the classification of sign-vehicles; which relies solely upon the judgments which theoretically, may range from perceptual discrimination to sheer guesses of analyst or group of analyst’s judgment are regarded as the report of the scientific observer. Finally, it is found that in urban society after coming of the industrialization era. The role and the position of ulama have changed. The ulama in urban society is not the social category again, but the parameter of ulama in urban society is the intellectual one. The position of ulama is not like a kyai or a teacher anymore such as what happened in pre-industrial or semi-industrial, but the ulama become the partner of people. Abstrak: Paper ini bermaksud untuk mengetahui perubahan pada masyarakat terkait dengan peran dan posisi ulama pada masyarakat urban. Masyarakat urban merupakan fenomena nyata pada era industrialisasi. Dengakn kata lain, masyarakat urban merupakan manifestasi dari masyarakat industrial. Penulis melihat fenomena yang serupa antara masyarakat urban dengan masyarakat industri. Tulisan ini merupakan riset kepustakaan yang mengambil sumber data dari buku dan literatur lain yang relevan. Sumber data diklasifikasi menjadi dua bagian, sumber data primer dan sumber data sekunder. Untuk analisis digunakan analisis isi yang mengklasifikasi tanda baca, yang didasarkan pada penilaian secara teoritis, berkisar dari diskriminasi persepsi sampai dugaan analisis atau kelompok penilaian analisis yang dipandang sebagai laporan ilmiah. Temuan dari penelitian ini bahwa masyarakat urban muncul sesudah era industrialisasi. Peran dan posisi ulama telah berubah. Ulama pada masyarakat urban bukan lagi semata pada kategori sosial, tetapi parameter ulama pada masyarakat urban ada pada aspek intelektualitasnya. Posisi ulama bukan lagi Kyai atau guru sebagaimana fenomena pada masyarakat pra industri atau semi industri, tetapi ulama menjadi patner masyarakat.